Tubular adenoma with high-grade dysplasia in the ileal segment 34 years after augmentation ileocystoplasty: report of a first case - Krasinskas Alyssa M; Armah Henry B; Parwani Anil V (BMC, 2007)
Abstract Neoplasms of the urinary bladder following augmentation ileocystoplasty are rare. We present the case of a 39-year-old male with a tubular adenoma with high-grade dysplasia in the ileal segment 34 years after augmentation ileocystoplasty to enlarge a post-chemoradiation-induced shrunken bladder. He presented with gross hematuria. Cystoscopy revealed a papillary tumor at the site of ileovesical anastomosis, and transurethral resection was performed. Histologic examination revealed a tubular adenoma with high-grade dysplasia. There are only two previous reports of tubulovillous adenoma in ileal segment after ileocystoplasty, both without high-grade dysplasia. Our observation supports the hypothesis that an ileal neobladder may undergo all the morphologic and molecular changes observed in the development of gastrointestinal adenocarcinoma. Therefore, patients who had an ileal neobladder created should be closely followed.